Formal and Informal Institutions in Wal-Mart Case - Vargas-hernández, José (JPAIR Multidisciplinary Research, 2013)
This paper analyzes the strategies which are followed by Wal-Mart in different parts of the world from the viewpoint of theories of institutions, property rights and agency. The analysis of the questions what happens to these firms when they are in countries with high corruption index? It could answer this question in light of the theory of institutions, the theory of property rights and the theory of the agency. This paper specifically focuses on finding out if the above theories are applicable. The analysis concludes that the same firm adopts a different strategy in each place even if is in conflict with their values at home.